Analysis Of Quality Control Of Raw Crackers Using Statistical Quality Control (Sqc) Method To Control Defective Products In Coconut Shrimp Crackers At Kelapa Gading Indramayu - Farchan, Fauzi; Tiara Fitri Rizkiya; Fitria Damayanti; Azzatillah, Azzatillah (ORGANIZE: Journal of Economics, Management and Finance, 2025)
Prawn Crackers Kelapa Gading Indramayu Indramayu is a company engaged in the food sector, especially the production of raw crackers. In the production process, there are still defective products, so the company needs quality control to reduce the failure rate. This study aims to assess whether the quality control implemented by Prawn Crackers Kelapa Gading Indramayu has been running optimally. The method used in this study is Statistical Quality Control (SQC), namely Control Chart, Fishbone diagram, and Pareto diagram to determine the level of factors causing damage, as well as to determine the types of damage that occur most frequently. The results of the control chart analysis show that the data obtained is still largely out of control. Based on the Fishbone diagram, the factors causing product damage come from human factors, raw material factors, method factors, machine factors, and environmental factors. While the Pareto diagram shows that the highest level of damage is caused by improper cutting of 87%